Building & running a successful research business : a guide for the independent information professional - Bates, Mary Ellen (CyberAge Books/Information Today, 2010)
The essential handbook for every information entrepreneur, this is the indispensable guide to launching, managing, and growing an independent research firm. From beginning to end, this newly updated study navigates through every stage of the process introductory procedures, conducting the company, the ideal marketing methods, and maximizing research. From making key decisions and closing the sale to maintaining good relationships with clients and tapping into powerful information sources beyond the Web, this first-rate collection of tips, tricks, and techniques is the key to building a success.